Vascular presentation of cystathionine beta-synthase deficiency in adulthood - Magner, Martin; Krupková, Lucie; Honzík, Tomáš; Zeman, Jiří; Hyánek, Josef; Kožich, Viktor (Journal of inherited metabolic disease, 2011)
Several recent studies describing a solely vascular presentation of cystathionine beta-synthase (CBS) deficiency in adulthood prompted us to analyze the frequency of patients manifesting with vascular complications in the Czech Republic. Between 1980 and 2009, a total of 20 Czech patients with CBS deficiency have been diagnosed yielding an incidence of 1:311,000. These patients were divided into three groups based on symptoms leading to diagnosis: those with vascular complications, with connective tissue manifestation and with neurological presentation. A vascular event such as a clinical feature leading to diagnosis of homocystinuria was present in five patients, while two of them had no other symptoms typical for CBS deficiency at the time of diagnosis. All patients with the vascular manifestation were diagnosed only during the past decade. The median age of diagnosis was 29 years in the vascular, 11.5 years in the connective tissue and 4.5 years in the neurological group. The ratio of pyridoxine responsive to nonresponsive patients was higher in the vascular (4 of 5 patients) and connective tissue groups (6 of 7 patients) than in the neurological group (2 of 8 patients). Mutation c.833T>C (p.I278T) was frequent in patients with vascular (6/10 alleles) and connective tissue presentation (8/14 alleles), while it was not present in patients with neurological involvement (0/16 alleles). During the last decade, we have observed patients with homocystinuria diagnosed solely due to vascular events; this milder form of homocystinuria usually manifests at greater ages, has a high ratio of pyridoxine responsiveness/nonresponsiveness, and the mutation c.833T>C (p.I278T) is often present.
Keywords: Homocystinuria; homocystinurie; Incidence; mladiství; Česká republika; Middle Aged; mužské pohlaví; incidence; Vascular Diseases; Adult; mladý dospělý; Czech Republic; dítě; Child; Child, Preschool; Young Adult; ženské pohlaví; nemoci cév; Humans; předškolní dítě; lidé středního věku; dospělí; Female; Adolescent; lidé; Male